2018
DOI: 10.1097/md.0000000000011000
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional prognostic scores in patients with hilar cholangiocarcinoma treated by percutaneous transhepatic biliary stenting combined with 125I seed intracavitary irradiation

Abstract: We mainly aimed to preliminarily explore the prognostic values of nutrition-based prognostic scores in patients with advanced hilar cholangiocarcinoma (HCCA).We retrospectively analyzed 73 cases of HCCA, who underwent percutaneous transhepatic biliary stenting (PTBS) combined with I seed intracavitary irradiation from November 2012 to April 2017 in our department. The postoperative changes of total bilirubin (TBIL), direct bilirubin (DBIL), alanine aminotransferase (ALT), aspartate aminotransferase (AST), alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Derived from total cholesterol, total lymphocyte count and serum albumin, it can assist in the assessment of nutritional status during hospitalization (37,38). In two studies of patients with hilar cholangiocarcinoma after intrahepatic cholangiocarcinoma and adjuvant therapy, a high CONUT score was identified as an independent predictor of poor OS prognosis (19,30). Similar to previous reports, univariate analysis in our study showed that preoperative PNI, NLR, and CONUT were associated with postoperative survival in HCCA patients.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Derived from total cholesterol, total lymphocyte count and serum albumin, it can assist in the assessment of nutritional status during hospitalization (37,38). In two studies of patients with hilar cholangiocarcinoma after intrahepatic cholangiocarcinoma and adjuvant therapy, a high CONUT score was identified as an independent predictor of poor OS prognosis (19,30). Similar to previous reports, univariate analysis in our study showed that preoperative PNI, NLR, and CONUT were associated with postoperative survival in HCCA patients.…”
Section: Discussionsupporting
confidence: 85%
“…Among them, the neutrophil lymphocyte ratio (NLR) and prognostic nutritional index (PNI) were considered to be independent prognostic factors that affect the survival of many malignancies (20)(21)(22)(23), and the Controlled Nutritional Status (CONUT) score, as an immune nutritional status scoring system that emerged in 2005, also took serum cholesterol into account when assessing the immune nutritional status of patients compared to PNI and NLR (24,25). The CONUT score, which is comprised of the serum values of albumin (ALB), total lymphocyte count (TLC), and total cholesterol, is considered to be a prognostic factor for postoperative prognosis of malignant tumors such as carcinoma of colon, non-small cell lung cancer, liver cancer and pancreatic ductal adenocarcinoma (26)(27)(28)(29), and has also been reported to be an important prognostic factor for survival in nonresectable HCCA (30).…”
Section: Introductionmentioning
confidence: 99%
“…In 1984, Onodera et al [26] have proposed that the linear predictive model relating the risk of operative complication and/or mortality to nutritional status is given by the relationship: PNI = 10 × serum albumin level (Alb) (g/dl) + 0.005 × total lymphocytes count (TLC)/mm3 in peripheral blood. PNI is simple to calculate, easy to interpret, and has been widely used to assess the preoperative immunologic and nutritional status of patients undergoing digestive surgery [27][28][29]. Our finding suggested that poor dental occlusal support might cause immunological and nutritional problems, leading to higher surgical risk and lower survival.…”
Section: Introductionmentioning
confidence: 70%
“…About one week later, PTBS with or without 125 I particles implantation were performed under digital subtraction angiography. The process has been described previously 14,15 . The dose delivered by 125 I particles implantation was approximately at 1 cm from the center of the radioactive source.…”
Section: Methodsmentioning
confidence: 99%